Windows Server Hybrid Administrator Associate (AZ-800) Cert Prep: 3 Implement and Manage an On-Premises and Hybrid Networking Infrastructure. - Rahman, Seema (linkedin.com, 2023)
Learn how to manage Windows Servers and workloads in a hybrid environment and get ready for the Microsoft AZ-800 exam.